Investigating the effect of DASH diet on blood pressure of patients with type 2 diabetes and prehypertension: Randomized clinical trial. Issue 1 (January 2019) - Hashemi, Reza; Rahimlou, Mehran; Baghdadian, Shiva; Manafi, Majid
Abstract: Background and objectives: Prehypertension in people with type 2 diabetes is associated with increased risk of cardiovascular disease and lower extremity damages compared to people with normal blood pressure. On the other hand, limited studies have conducted to investigate the effect of DASH diet on blood pressure and prehypertension in patients with type 2 diabetes. Therefore, in this study, we aimed to evaluate the effect of DASH diet on blood pressure and prehypertension in patients with type 2 diabetes. Materials and methods: In this clinical trial, 80 patients with diabetes type 2 and prehypertension in the age range of 18–65 years were randomly allocated to intervention (n = 40) and control (n = 40) groups for 12 weeks. The intervention group had DASH diet and the control group received diabetic diet in accordance with the recommendations of the American Diabetes Association (ADA) with 24-h dietary recall; systolic and diastolic blood pressures were measured before and after study. Results: Taking DASH diet and diabetic diet for 12 weeks caused significant reduction in systolic blood pressure in the intervention group (P value = 0.003). Diastolic blood pressure showed no significant change in none of the two groups. Conclusion: Following the DASH diet in patients with prehypertension has beneficial effects in improving systolic blood pressure and can be effective to prevent the development of hypertension. Hence, there are needs for long-term interventions with larger sample size in future studies.